plz do it anyone...correct answer will be marked as brainliest and his or her account will be followed
Attachments:
![](https://hi-static.z-dn.net/files/d7a/d62703cef5d8ba95d1f5460173c8ef0c.jpg)
Answers
Answered by
0
Answer:
Step-by-step explanation:
Mark me as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d73/6da78d872d86a3ca9b9e9fa3b881cb42.jpg)
Answered by
0
Answer:
assume # to be theta
LHS = ( sin # - 2 sin³ # ) / ( 2 cos³# - cos # )
= ( sin # { 1 - 2 sin²# } ) / ( cos # { 2 cos²# - 1 } )
= ( sin #{ sin²# + cos²# - 2 sin²# } ) / ( cos # { 2 cos² # - [sin² # + cos²# ] } )
= ( sin #{ sin²# + cos²# - 2 sin²# } ) / ( cos # { 2 cos² # - sin² # - cos²# } )
because 1 = sin²# + cos² #
= ( sin # { cos²# - sin²# } ) / ( cos # { cos²# - sin²# } )
{ cos²# - sin²# } and { cos²# - sin²# } will be cancelled in numerator and denominator
= sin # / cos #
= tan #
= RHS
hence proved
Similar questions